PENINGKATAN KEMAMPUAN BERBICARA ANAK MELALUI MEDIA GAMBAR BERSERI TEMA BENCANA DI TAMAN KANAK-KANAK HARAPAN PKK BENGKULU UTARA - Hikma Juli; Syahrul Ismet (STKIP Subang, 2026)
The speaking ability of Group B children at Harapan PKK Kindergarten, Kota Agung Village, North Bengkulu, had not developed optimally. Most children struggled to express ideas in simple sentences, lacked confidence speaking in front of teachers and peers, and tended to respond with a single word. This study aimed to improve the speaking ability of Group B children through disaster-themed serial picture media reflecting children's everyday experiences. The study used a Classroom Action Research (CAR) design following the Kemmis and McTaggart model, consisting of planning, acting, observing, and reflecting across two cycles. The subjects were 10 Group B children selected through saturated sampling. Data were collected through observation and documentation using a rubric covering three indicators—speaking courage, speaking fluency, and the ability to retell events sequentially according to the pictures—then analyzed descriptively and quantitatively. The results showed a consistent improvement, from 32.5% in the baseline observation (emerging category) to 63.3% in Cycle I (developing as expected) and 80% in Cycle II (developing very well). The largest gains occurred in speaking fluency and retelling ability. The study concludes that disaster-themed serial picture media effectively improves Group B children's speaking ability while introducing basic disaster-related knowledge from an early age, offering a contextual learning media alternative for early childhood educators in disaster-prone areas.